2023
DOI: 10.31557/apjcp.2023.24.2.613
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Gene Polymorphisms od the XRCC1 and TP53 with the Gender of Children with Acute Leukemia

Abstract: Background:The relevance of the study lies in the fact that although the role of polymorphism of some genes that are responsible for cell apoptosis and deoxyribonucleic acid repair in the development of acute leukemia has already been established, its relationship with the gender of patients has not been studied enough. This study was aimed at studying the relationship between the Arg399Gln polymorphism in the XRCC1 deoxyribonucleic acid repair gene and the Arg72Pro polymorphism in the TP53 tumor suppressor ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
(33 reference statements)
0
1
1
Order By: Relevance
“…In a study conducted with children with acute leukaemia, it was investigated whether there was a relationship between gender and being ill, but no relationship was found [48]. In our study, no relationship was found between gender and being ill ( p>0.05) (Table 1).…”
Section: Discussioncontrasting
confidence: 54%
“…In a study conducted with children with acute leukaemia, it was investigated whether there was a relationship between gender and being ill, but no relationship was found [48]. In our study, no relationship was found between gender and being ill ( p>0.05) (Table 1).…”
Section: Discussioncontrasting
confidence: 54%
“…A previous study conducted in Sudan has reported an association between Arg/Pro genotype and risk of both CLL and acute lymphoblastic leukemia (ALL) (45). Also, a Moroccan study has detected a protective effect of Arg/Arg and the Arg/Pro genotypes (46).…”
Section: Discussionmentioning
confidence: 98%